Topical issues of improving the media of creativity of a future teacher - Babadjanov Salokhiddin Sabitdjanovich (Research Parks Publishers, 2021)
This article is aimed at the scientific interpretation of a methodical project to improve the future teacher’s mediocreativity. Together with this, the results of the level of development of the mediation capacity are presented